Application of Blended Learning Methods in Increasing High School Students' Learning Interest in Sukoharjo - Sinta Anggun Lestari; Poni Poni Poni; Pranichayudha Rohsulina Rohsulina (Journal of Geography Science and Education, 2021)
The Covid-19 pandemic caused a change in the education system that began from face-to-face meetings in the classroom to online-based to reduce the spread of the covid-19 virus. During online learning this causes the interest in learning learners decrease and there are several obstacles, namely: facilities, facilities, and infrastructure that are less supportive in teaching and learning activities, in addition to the lack of teaching methods carried out by educators in learning activities. This research uses descriptive research methods with quantitative approaches as well as primary data collection techniques from tests (questionnaires) and observation of online and offline learning activities in the classroom. Sma Negeri 1 Tawangsari has implemented a learning system offline and online. So that the application of blended learing learning methods is considered suitable in this system. Supported by the results of research shown in the second cycle that showed that offline learning activities are more desirable to learners because of the interaction between teachers and participants who are able to improve memory, reduce smartphone use that causes negative impacts on health, and short assignments with long-term collection.